2010
DOI: 10.1039/c0nr00416b
|View full text |Cite
|
Sign up to set email alerts
|

Single-step synthesis and magnetic separation of graphene and carbon nanotubes in arc discharge plasmas

Abstract: The unique properties of graphene and carbon nanotubes made them the most promising nanomaterials attracting enormous attention, due to the prospects for applications in various nanodevices, from nanoelectronics to sensors and energy conversion devices. Here we report on a novel deterministic, single-step approach to simultaneous production and magnetic separation of graphene flakes and carbon nanotubes in an arc discharge by splitting the high-temperature growth and low-temperature separation zones using a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 27 publications
0
70
0
Order By: Relevance
“…Graphene flakes and sheets have shown a high electrical conductivity, a high theoretical SSA of 2630 m 2 /g and a very high intrinsic electrical conductivity in plane as well as high mechanical strength and chemical stability comparable with or even better than CNT [77,78]. Generally speaking, there are four approaches to synthesize graphene for the application of EC, that is, mechanical exfoliation from bulk graphite [15], arc discharge [79], chemical vapor deposition and epitaxial growth, [80,81] and reduction of graphite oxides [82]. The synthesis of graphene by exfoliation of graphite is not in large scale so that it is only suitable for fundamental study so far.…”
Section: Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Graphene flakes and sheets have shown a high electrical conductivity, a high theoretical SSA of 2630 m 2 /g and a very high intrinsic electrical conductivity in plane as well as high mechanical strength and chemical stability comparable with or even better than CNT [77,78]. Generally speaking, there are four approaches to synthesize graphene for the application of EC, that is, mechanical exfoliation from bulk graphite [15], arc discharge [79], chemical vapor deposition and epitaxial growth, [80,81] and reduction of graphite oxides [82]. The synthesis of graphene by exfoliation of graphite is not in large scale so that it is only suitable for fundamental study so far.…”
Section: Graphenementioning
confidence: 99%
“…In light of the introduction of magnetic field in arc, our research group presented an approach to synthesize the composite production of carbon nanotubes and graphene simultaneously in a non-uniformed magnetically-enhanced arc discharge, for the purpose of utilization of excellent properties of SWCNT and graphene together [79,101,102]. The paper-based electrodes of ultracapacitor were fabricated by wire wound rod coating method with the ink of the composites and exhibited advantage in contrast to the thin electrodes only made from SWCNT synthesized without magnetic field.…”
Section: One-step Synthesis In Arcmentioning
confidence: 99%
“…The fall-out during the discharge process is the end product that contains the carbon nano-structures. Volotskova et al [22] have reported on deterministic, single-step approach to simultaneous production and magnetic separation of graphene flakes and carbon nanotubes. In this arc discharge process, by employing magnetic fields, nanotubes and graphene are deposited in different areas.…”
Section: Arc Dischargementioning
confidence: 99%
“…It has been shown to successfully synthesize graphene flakes with and without the enhancement of a magnetic field. 25,26,27,28,29,30,31 Graphene was synthesized using anodic arc ablation in a helium environment at atmospheric pressure. Samples were collected from the chamber wall or the surface of the magnet, and were characterized with SEM, TEM, AFM and RAMAN spectroscope.…”
Section: Introductionmentioning
confidence: 99%